Development and Validation of Stability Indicating Liquid Chromatographic Method for Simultaneous Estimation of Silodosin and Dutasteride in API and Combined Dosage Form - Rathod, Sapna; Shah, Ayushi; Patel, Nisarg; Mehta, Maulik; Prajapati, Bhupendra (Indian Journal of Pharmaceutical Education and Research)
Background: The proposed work was done with a view to develop a RP-HPLC approach for the concurrent quantification of Dutasteride and Silodosin in API and capsule formulation and validate it. Materials and Methods: A C18 Thermo BDS column (150×4.6 mM, 5 μM) was utilized, which also used buffer and acetonitrile as mobile phase (70:30 v/v) eluent A and (30:70 v/v) eluent B at flow rate of 1 mL/min. The samples were quantified at 250 nm employing a PDA detector. In compliance with ICH recommendations, the methodology was validated. Results: For DUT and SIL, linear response was obtained in the range of 5-15 μg/mL and 40-120 μg/mL, individually. The LOD and LOQ values of DUT and SIL were respectively observed 0.302 μg/mL, 1.859 μg/mL and 0.909 μg/mL, 5.634 μg/mL. Both drugs had assay results that ranged from 99.13 to 99.79%. Stress testing using acid, base, peroxide, light and heat were carried out. After adequate treatment, these mixtures were injected in HPLC and it was revealed that products generated from the stress studies were resolved from the peaks of analyte. Conclusion: The current approach was considered accurate, robust, linear, specific and precise and it can be utilized for the concurrent investigation of the drugs stated in its capsule.
Keywords: Dutasteride; Forced Degradation; Simultaneous estimation; Stability Indicating RP-HPLC Method Silodosin.